Przebieg pogody w Hornsundzie podczas wyprawy PAN „Spitsbergen 1982/83” - Stepko, Waldemar; Rodzik, Jan (nakł. Uniwersytetu Marii Curie-Skłodowskiej, 1986)
Artykuł w: Annales Universitatis Mariae Curie-Skłodowska. Sectio B, Geographia, Geologia, Mineralogia et Petrographia. Vol. 40 (1985), s. 33-53 streszcz. ang., ros. tyt. równol.: The Weather Course in Hornsund During the Polish Academy of Science Expedition to Spitsbergen in 1982/83 Artykuł w: Annales Universitatis Mariae Curie-Skłodowska. Sectio B, Geographia, Geologia, Mineralogia et Petrographia. Vol. 40 (1985), s. 33-53 streszcz. ang., ros. tyt. równol.: The Weather Course in Hornsund During the Polish Academy of Science Expedition to Spitsbergen in 1982/83